For f(x), 6 represents x here, so we plug 6 in for x to get 2*6²+5√(6-2). Using PEMDAS, we get 72+5√4=72+5*2=72+10=82
The answer should be 32.25

x² - x - 12 ≠ 0
x² - 4x + 3x - 12 ≠ 0
x (x - 4) + 3 (x - 4) ≠ 0
(x + 3)(x - 4) ≠ 0
x ≠ -3 or x ≠ 4
(B)
Answer:
-sqrt(3) -i = 2 cis (7pi/6)
Step-by-step explanation:
-sqrt(3) -i
We can find the radius
r = sqrt( (-sqrt(3)) ^2 + (-1) ^2)
= sqrt( 3 + 1)
= sqrt(4)
= 2
theta = arctan (y/x)
arctan (-1/-sqrt(3))
arctan (1/sqrt(3))
theta = pi/6
But this is in the first quadrant, and we need it in the third quadrant
Add pi to move it to the third quadrant
theta = pi/6 + 6pi/6
=7pi/6
-sqrt(3) -i = 2 cis (7pi/6)
3/4 times 1 1/2 = 1 1/8
Hope this helps!